PEMETAAN PASAR TRADISIONAL DI WILAYAH PESISIR SEBAGAI PUSAT PERBELANJAAN MASYARAKAT KABUPATEN BONE BOLANGO - Melo, Ramla Hartini; Laudji, Muhammad Alfian; Niode, Syarifah Fatimah Setiasih (Jurnal Pendidikan dan Ekonomi (JUPEK), 2023)
Bone Bolango Regency, located in the coastal area, is known to have various traditional markets that function as trading centers for the local community. These markets play a vital role in the local economy, providing a place for traders to sell various commodities, from agricultural and fishery products to basic necessities. This study aims to create a map of the distribution of traditional markets in the coastal area of Bone Bolango Regency, using a mapping method approach through Geographic Information Systems (GIS). GIS is a very useful tool in mapping these markets. The results of the study show that mapping of traditional markets in Bone Bolango Regency can be easily accessed through GIS. Integration of spatial and attribute data produces maps that are not only informative but also interactive. Data on market location, infrastructure, accessibility. displayed visually.